Association between knowledge of cardiovascular disease and healthy life style among hypertensive patients attending outpatient clinic of Universiti Sains Malaysia Hospital - Arinima, Punitha (2017)
Association between healthy life style and knowledge of cardiovascular disease among hypertensive patients attending outpatient clinic of Universiti Sains Malaysia Hospital. Introduction: Hypertension is one of the risk factors for cardiovascular disease. Having good knowledge is believed to be fundamental for one to practice a healthy life style as a preventive effort. However, there is limited data available on the level of knowledge of cardiovascular disease among hypertensive patients and studies on the preventive measures for healthy life style among the Kelantanese. Hence, this study was performed to assess the association between the healthy life style and knowledge of cardiovascular disease among the hypertensive patients attending outpatient clinic of Hospital Universiti Sains Malaysia. Objective: To determine the association between healthy life style (dietary practice, smoking and physical activity) and the knowledge of cardiovascular disease among hypertensive patients. Methodology: This is a cross sectional study involving 314 hypertensive patients attending outpatient clinic of USM Hospital from September to December 2015. Those who fulfilled the inclusion and exclusion criteria were then selected via systemic random sampling. The hypertensive patients were interviewed based on a set of questionnaires consist of questions on socio demographic, knowledge on cardiovascular disease and healthy life style, which includes dietary, smoking status and physical activity. The sociodemographic data was analysed using descriptive statistic. Data foreach objective was analysed with the simple logistic regression. The association between variables were analysed with multiple logistic regression. Results:The proportion of hypertensive patients who followed the recommended dietary practice, non-smoker and physically active are 7.3%, 92% and 34.4% respectively. Meeting the dietary recommendations was not associated with knowledge (OR = 0.7; CI95% 0.28;1.75). There was no significant association between smoking and cardiovascular knowledge (OR = 0.9; CI95% 0.39;2.09). There was no significant association between physical activity and knowledge (OR = 21.5; CI95% 0.43;1.14) Conclusion: Knowledge of cardiovascular disease among the hypertensive patients is not significantly associated with healthy lifestyle i.e. dietary practice, smoking and physical activity. This suggests that other factors that may contribute to healthy lifestyle has to be identified and studied.